Enhancing IT maturity in the Devops focus area: A comprehensive assessment with COBIT 2019 - Febrianti, Febby; Nugeraha Utama, Ditdit (Edelweiss Applied Science and Technology, 2024)
The research will investigate the following research inquiries: by utilizing the COBIT 2019 design toolkit, what is the level of DevOps maturity within the company according to COBIT 2019, and what recommendations are required to enhance the maturity level in DevOps. The researchers conducted a collaborative workshop with the critical management team to obtain reliable and accurate information. The workshop engaged participants from the development and operations teams to gather and analyze data about current DevOps practices. Based on the data, it is known that out of the 26 processes within the DevOps focus area, they have been measured and resulted in a maturity level of 3.15. The value of 3.15 indicates that the DevOps maturity level falls under the ''Defined'' category, meaning that the processes within the DevOps focus area have been implemented consistently. The case study research has reached its outcomes, and the researcher can conclude that the study has successfully achieved its objectives and benefits. This research has conducted an assessment of the maturity level for the DevOps focus area using the Process Assessment Model (PAM) as a measurement tool.